Transposition of the Segregationist Colonial System on Social Housing: Case of the Diar El Mahçoul-Algiers City - Merzelkad-Hallal, Rym; Merzelkad-Nedjai, Kahina (Future Science, 2024)
The French colonial system in Algeria was a political system based on the establishment of political, economic, social and cultural domination of the colonists over the colonized people (G.Pervillie, 1975). In concrete terms, it resulted in the establishment of a set of discriminatory norms tending to grant privileges to European settlers to the detriment of Algerians in all areas of social life. This organized discrimination was at the origin of a visible social inequality that materialized through spatial segregation aimed at separating Algerians from settlers (T.Guillope, 2020). In fact, the European districts benefited from infrastructures that almost systematically included public services in a high quality designed urban environment. While the Algerian neighbourhoods benefited from very little public investment. The juxtaposition of this discriminatory notion on the architectural and urban design of the district of Diar El Mahçoul is a perfect illustration of this, which makes it an ideal case to be examined in this article.